2017
DOI: 10.7874/jao.2017.21.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Effect of Eggshell Membrane Patching for Moderate-to-Large Traumatic Tympanic Membrane Perforation

Abstract: Background and ObjectivesTo evaluate the effect of eggshell membrane (ESM) patching for tympanic membrane (TM) perforation, and to investigate correlations between healing time and age, gender, patching time, perforation size, and perforation location.Subjects and MethodsOne hundred and seventy-five patients diagnosed with traumatic TM perforation at the Department of Otorhinolaryngology-Head and Neck Surgery, Korea University Ansan Hospital, between January 2008 and October 2013. Patients were divided into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
0
15
1
Order By: Relevance
“…5–7 Early edge approximation has been reported to restore the original anatomy and reduce the perforation size, thereby facilitating the healing process and shortening the closure time of traumatic tympanic membrane perforations. 6–9 However, in the present study, the closure rate was not significantly different between edge approximation subgroup A (reversed edge of more than 50 per cent of the total perforation), edge approximation subgroup B (reversed edge of less than 50 per cent of the total perforation) and the spontaneous healing group. In addition, the closure time was not significantly different between edge approximation subgroups A and B, and there was no significant correlation between the healing outcome and the reversed edge area.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…5–7 Early edge approximation has been reported to restore the original anatomy and reduce the perforation size, thereby facilitating the healing process and shortening the closure time of traumatic tympanic membrane perforations. 6–9 However, in the present study, the closure rate was not significantly different between edge approximation subgroup A (reversed edge of more than 50 per cent of the total perforation), edge approximation subgroup B (reversed edge of less than 50 per cent of the total perforation) and the spontaneous healing group. In addition, the closure time was not significantly different between edge approximation subgroups A and B, and there was no significant correlation between the healing outcome and the reversed edge area.…”
Section: Discussioncontrasting
confidence: 66%
“…Some research groups have suggested that early edge approximation facilitates eardrum healing and shortens closure time. 59 However, there have been no previous detailed studies on the correlation between healing outcome and the size of the everted or inverted edge. Typically, barotraumas in peacetime are caused by a slap or the impact of a fist on the ear.…”
Section: Introductionmentioning
confidence: 99%
“…Because previous study reported that eggshell membrane presented an excellent healing effect for tympanic membrane defect and healing time was significantly shorter in the eggshell membrane patch. 5…”
Section: Morphological Observationmentioning
confidence: 99%
“…However, there are many disadvantages associated with the conventional treatment modality, which involves cost, risk, defective donor sites, and the inconvenience of an operation. 5 Therefore, a type of noninvasive treatment, such as TM patch application, is usually selected as initial treatment. A variety of autografts, allografts and xenografts, such as paper patch, eggshell membrane, fascia temporalis, tragus perichondrium, acellular dermal allograft, are a few established options for treating TM perforations [5][6][7][8][9] (Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation